Assessment of the origin and geothermal potential of the thermal waters by hydro-isotope geochemistry: Eskisehir province, Turkey. Issue 2 (4th March 2017) - Yuce, Galip; Italiano, Francesco; Yasin, Didem; Taskiran, Lutfi; Gulbay, Ahmet Hilmi
ABSTRACT: The thermal fluids vented over Eskisehir province have been investigated for their origin and to estimate the geothermal potential of the area. Thermal waters as well as bubbling and dissolved gases were collected and analysed for their chemical and isotopic features. Their isotopic composition varies in the range from −11.5 to −7.7 ‰ for δ 18 O, −84 and −57 ‰ for δ 2 H, and 0–7.2 TU for tritium. The gases (bubbling and dissolved) are mostly N2 -dominated with a significant amount of CO2 . The helium isotopic ratios are in the range of 0.2–0.66 R/Rac, indicate remarkable mantle-He contribution ranging between 2 and 10 % in the whole study area. Considering the estimated geothermal gradient about three times higher than the normal gradient, and the reservoir temperatures estimated to be between 50 and 100 °C using quartz and chalcedony geothermometers, a circulation model was built where possible mixing with shallow waters cool down the uprising geothermal fluids.